MENGUKUR KEPUASAN MAHASISWA DALAM MENGGUNAKAN APLIKASI MUSIC STREAMING MENGGUNAKAN METODE AHP (INTI Nusa Mandiri, 2024)
Online streaming applications are currently very popular among the public, especially students. Because of this user interest, the author wanted to conduct research. This research uses the AHP method to measure students' level of satisfaction with the use of music streaming applications. The research evaluation criteria included quality, service, price and payment. Questionnaires are used to determine student preferences and assessment of related criteria. The collected data was analyzed using the AHP method and the application priorities were compared. These findings will help developers and users improve quality and user experience. The research was conducted using the Analytical Hierarchy Process (AHP) methodology on students in the Bekasi City area with a population of 7058 people and obtained a sample size of 379 respondents using the Slovin formula. The research results show that Spotify is the most popular music streaming application among users, especially students. Followed by applications such as Joox and YouTube.
Keywords: AHP; music; satisfaction